Intelligent Systems Design and Applications Natural Language Processing, Volume 4 - Abraham, Ajith; Bajaj, Anu; Hanne, Thomas; Siarry, Patrick (Lecture Notes in Networks and Systems, 2024)
XVII, 483 p. 246 illus., 143 illus. in color.